The integration of single-cell sequencing, TCGA, and GEO data analysis revealed that PRRT3-AS1 is a biomarker and therapeutic target of SKCM - Zhang, Wancong; Xie, Xuqi; Huang, Zijian; Zhong, Xiaoping; Liu, Yang; Cheong, Kit-Leong; Zhou, Jianda; Tang, Shijie (Frontiers in Immunology, 2022)
Introduction: Skin cutaneous melanoma (SKCM) is the world’s fourth deadliest cancer, and advanced SKCM leads to a poor prognosis. Novel biomarkers for SKCM diagnosis and prognosis are urgently needed. Long non-coding RNAs (lncRNAs) provide various biological functions and have been proved to play a significant role in tumor progression. Single-cell RNA sequencing (scRNA-seq) enables genome analysis at the single-cell level. This study explored prognostic lncRNAs in SKCM based on scRNA-seq and bulk RNA sequencing data. Materials and Methods: The TCGA cohort and melanoma samples in the GEO database (GSE72056, GSE19234, GSE15605, GSE7553, and GSE81383) were included in this study. Marker genes were filtered, and ensemble lncRNAs were annotated. The clinical significance of selected lncRNAs was verified through TCGA and GEO dataset analysis. SiRNA transfection, cellular viability, wound‑healing, colony formation and transwell assays were performed to evaluate the effect of PRRT3-AS1 on cellular function. Immune infiltration of the selected lncRNAs was also exhibited. Results: A 5-marker-lncRNAs model of significant prognostic value was constructed based on GSE72056 and the TCGA cohort. PRRT3-AS1 combined with DANCR was then found to provide significant prognostic value in SKCM. PRRT3-AS1 was filtered for its higher expression in more advanced melanoma and good prognosis value. Cellular function experiments in vivo revealed that PRRT3-AS1 promotes proliferation, migration and invasion in SKCM. PRRT3-AS1 was found to be related to epithelial-mesenchymal transition (EMT) signaling pathways. DNA methylation of PRRT3-AS1 was negatively related to PRRT3-AS1 expression and showed good prognosis value. In addition, PRRT3-AS1 may suppress immune infiltration and be involved in immunotherapy resistance. Conclusion: PRRT3-AS1 may be a diagnostic and prognostic biomarker of SKCM.